The relative strength of common synaptic input to motor neurons is not a determinant of the maximal rate of force development in humans - Del Vecchio, Alessandro; Falla, Deborah; Felici, Francesco; Farina, Dario (Journal of Applied Physiology, 2019)
Correlation between motor unit discharge times, often referred to as motor unit synchronization, is determined by common synaptic input to motor neurons. Although it has been largely speculated that synchronization should influence the rate of force development, the association between the degree of motor unit synchronization and rapid force generation has not been determined. In this study, we examined this association with both simulations and experimental motor unit recordings. The analysis of experimental motor unit discharges from the tibialis anterior muscle of 20 healthy individuals during rapid isometric contractions revealed that the average motor unit discharge rate was associated with the rate of force development. Moreover, the extent of motor unit synchronization was entirely determined by the average motor unit discharge rate (R 0.7, P 0.0001). The simulation model demonstrated that the relative proportion of common synaptic input received by motor neurons, which determines motor unit synchronization, does not influence the rate of force development (R 0.03, P 0.05). Nonetheless, the estimates of correlation between motor unit spike trains were significantly correlated with the rate of force generation (R 0.8, P 0.0001). These results indicate that the average motor unit discharge rate, but not the degree of motor unit synchronization, contributes to most of the variance of human contractile speed among individuals. In addition, estimates of correlation between motor unit discharge times depend strongly on the number of identified motor units and therefore are not indicative of the strength of common input.
CRIS-Team Scopus Importer:2020-10-12
Keywords: Ballistic contractions; Common synaptic input; EMG decomposition; Motor neurons; Motor unit synchronization; Neural drive